Measurement of quality-of-life perception regarding satisfaction with public transport in Costa Rica - Allen, Jaime (2025)
The issue of mobility is increasingly important in Costa Rica; therefore, it becomes relevant to improve the public transport system in the country. To determine which elements of the public transport system in Costa Rica affect the quality of life according to the users′ perception, it is essential to know their opinion regarding the conditions in which the service is provided. To identify the components of the structure of the public transport system in Costa Rica that have a greater impact on the quality of life of its users, the results of a survey on the effect of the use of public transport on quality of life were analysed. The data were collected by means of a questionnaire applied to workers and students at the University of Costa Rica (UCR). Structural Equation Models (SEM) were used as an analysis tool, which are a multivariate statistical tool that allows studying the relationship between latent and observed variables. The SEM allowed verifying that satisfaction with the use of public transport is a domain that affects satisfaction with the quality of life, in other words, for Costa Ricans, the perception of being satisfied with their quality of life is influenced by the perception of satisfaction they have with the use of public transport.